2013
DOI: 10.5132/eec.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Fish histopathology as biomarker to evaluate water quality

Abstract: Aquatic environments contaminated by industrial effluents and urban sewage present as common characteristic the release of xenobiotics complex mixture that potentially affects important aspects related with physiological aspects in fish. In the present work, fish specimens, Astyanax aff. fasciatus and Oreochromis niloticus, were used to evaluate the anthropogenic impact in two lakes (Lake Park and Cedeteg) situated in Guarapuava City, southern of Brazil. The occurrence of morphological changes in gills and liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 34 publications
3
30
0
10
Order By: Relevance
“…Conversely, decreased CF has been recorded in several disturbed sites, such as, for the Atlantic cod, Gadus morhua Linnaeus, 1758 exposed to petroleum (Kiceniuk & Khan, 1987), for white sucker (C. commersoni) in sites with high concentration of metals Cu and Zn (Munkittrick & Dixon, 1988;Miller, Munkittrick & Dixon,1992). In accordance with Liebel et al (2013), CF is an indicative of the health status and may be used to assess field contamination. Alterations in growth rates are induced by contaminants and the explanation is the reallocation of energy to detoxification mechanisms, depleting reserves that were originally destined for growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, decreased CF has been recorded in several disturbed sites, such as, for the Atlantic cod, Gadus morhua Linnaeus, 1758 exposed to petroleum (Kiceniuk & Khan, 1987), for white sucker (C. commersoni) in sites with high concentration of metals Cu and Zn (Munkittrick & Dixon, 1988;Miller, Munkittrick & Dixon,1992). In accordance with Liebel et al (2013), CF is an indicative of the health status and may be used to assess field contamination. Alterations in growth rates are induced by contaminants and the explanation is the reallocation of energy to detoxification mechanisms, depleting reserves that were originally destined for growth.…”
Section: Discussionmentioning
confidence: 99%
“…The HSI is one of indices most often associated with exposure to contaminants (Grady, Mclaughlin, Caldwell, Schmitt, & Stalling, 1992;Hismayasari, Marhendra, Rahayu, Saidin & Supriyadi, 2015). Likewise, the liver is a primary detoxification organ in fish (Hinton & Laurén, 1990;Liebel et al 2013) and an important target organ related to important metabolic mechanisms. According to Casarett, Amdur, Klaassen, and Doull (1991), the liver is the main organ related to biotransformation process of xenobiotics, by increasing in size (hypertrophy), increasing the number of hepatocytes (hyperplasia) or both in polluted areas (Goede & Barton, 1990;Hinton & Lauren;Sudarshan & Kulkarni, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That procedure has been widely accepted and applied for histopathology-based evaluation of water pollution (Liebel et al 2013;Lujić et al 2015;Rašković et al 2015). Since chemical and microbiological water quality of three rivers in north-eastern Macedonia which were selected for this study, Bregalnica, Zletovska and Kriva, was determined simultaneously with chub sampling (Ramani et al 2014), we were able to associate observed histopathological alterations to specific degrees and types of water contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic organisms, including fish, serve as valuable bio-indicators of ecosystem health (Whitfield and Ellis 2002;Pusey et al 2007;Jia and Chen 2013). Specifically, fish body condition indices and histological biomarkers (Thilakaratne et al 2007;Liebel et al 2013) have been used to monitor anthropogenic disturbances in ecosystems. However a paucity of knowledge on spatial and temporal variations in fish pathobiology is limiting the extent to which information collected from monitoring programs can be meaningfully interpreted (Cajaraville et al 2000;Whitfield and Elliot 2002).…”
Section: Introductionmentioning
confidence: 99%